Magnesium sulfate pharmacokinetics after intramuscular dosing in women with preeclampsiaAJOG Global Reports at a Glance - Kathleen Brookfield, MD, PhD, MPH (AJOG Global Reports, 2021)
BACKGROUND: Current intramuscular magnesium dosing regimens in low and middle-income countries are based on indirect absorption parameters to inform pharmacokinetic and pharmacodynamic response. OBJECTIVE: To determine if therapeutic serum magnesium levels are obtained in women with severe preeclampsia receiving intramuscular administration of magnesium sulfate using the Pritchard regimen and to compare the key pharmacokinetic variables to those previously published. STUDY DESIGN: Serum magnesium levels were obtained at multiple time points at baseline and after magnesium sulfate administration from women with severe preeclampsia receiving the standard Pritchard regimen for seizure prophylaxis at Bayero University, Kano, Nigeria. The pharmacokinetic profiles were constructed for the study cohort and the updated pharmacokinetic model was compared with the one that was previously published. RESULTS: A total of 80 blood samples were collected from 20 women with severe preeclampsia (45 collected before childbirth and 35 collected after childbirth). After 11.5 hours of magnesium sulfate administration, 63% of women in the cohort had serum magnesium levels of ≥2.0 mmol/L. Data from women receiving the Pritchard regimen combined with data from women previously modeled after the receipt of intravenous magnesium sulfate were adequately described using a 2-compartment model with first-order absorption and linear elimination from the central compartment. All structural pharmacokinetic parameters including clearance, central volume of distribution, peripheral volume of distribution, and intercompartment clearance were adjusted for maternal weight, and the clearance was further adjusted for serum creatinine level and antepartum or postpartum status. The simulated pharmacokinetic profiles of the updated pharmacokinetic model and the previously published pharmacokinetic model are similar. In previously published pharmacokinetic modeling, absorption rate constant=0.32 and absolute bioavailability=0.86. In the updated pharmacokinetic model, absorption rate constant=0.45 and absolute bioavailability=0.91. CONCLUSION: These data support the use of the Pritchard regimen as acceptable to achieve therapeutic serum magnesium levels and support the reported simulation of serum magnesium levels and eclampsia response associated with different intramuscular regimens.